2019
DOI: 10.1007/s10792-019-01074-z
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ultrawide-field fundus ophthalmoscopy-assisted deep learning for detecting treatment-naïve proliferative diabetic retinopathy

Abstract: Purpose We investigated using ultrawide-field fundus images with a deep convolutional neural network (DCNN), which is a machine learning technology, to detect treatment-naïve proliferative diabetic retinopathy (PDR). Methods We conducted training with the DCNN using 378 photographic images (132 PDR and 246 non-PDR) and constructed a deep learning model. The area under the curve (AUC), sensitivity, and specificity were examined. Result The constructed deep learning model demonstrated a high sensitivity of 94.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…At present, UWF imaging techniques have had a wide range of applications in the diagnosis of DR. Studies have found that early damage of DR can be observed in the peripheral region of retina, such as the appearance of haemorrhage, IRMA and so on 79 . Optos ultrawidefield (Optos plc) allows the photography to capture a 200‐degree field of view, which accounts for about 80% of the retina.…”
Section: Performance Of Dl‐based Dr Algorithms By Other Screening Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, UWF imaging techniques have had a wide range of applications in the diagnosis of DR. Studies have found that early damage of DR can be observed in the peripheral region of retina, such as the appearance of haemorrhage, IRMA and so on 79 . Optos ultrawidefield (Optos plc) allows the photography to capture a 200‐degree field of view, which accounts for about 80% of the retina.…”
Section: Performance Of Dl‐based Dr Algorithms By Other Screening Devicesmentioning
confidence: 99%
“…The automated algorithm achieved a sensitivity of 90.3%, a specificity of 53.6% and the AUC of 0.851 for detecting referral‐warranted retinopathy. In 2019, Nagasawa et al 79 trained a CNN model to detect treatment‐naïve PDR in UWF photography. The constructed model demonstrated a high sensitivity of 94.7% and a high specificity of 97.2%, with an AUC of 0.969.…”
Section: Performance Of Dl‐based Dr Algorithms By Other Screening Devicesmentioning
confidence: 99%
“…Retinal vein occlusion, high myopia, glaucoma, and diabetic retinopathy (DR) are common ophthalmological diseases that can usually be diagnosed through fundus images. [1][2][3] Retinal vein occlusion is the most common fundus vascular disease in the elderly and treatment timely may avoid blindness. There are many groups of myopia in China.…”
Section: Introductionmentioning
confidence: 99%
“…UWF, otherwise known as Optos (Optos 200Tx; Optos Plc, Dunfermline, United Kingdom), is a non-contact, noninvasive imaging modality that can capture up to 200°of visible fundus and has become essential for understanding and managing the peripheral retinal pathologies of adult diseases such as diabetes and retinal vein occlusions [16,17]. Indeed, one report showed the accuracy of UWF-based AI in the detection of DR [18].…”
Section: Introductionmentioning
confidence: 99%